Earthquake Rescue Mission Modeling Based on Multi-Agent - Jing Zang; Hu Liu; Xianping Ni (Institute of Advanced Engineering and Science, 2014)
In order to better research the role helicopter played in the earthquake rescue, a helicopter earthquake rescue mission modeling method based on multi-agent was proposed. The elements of the earthquake environment modeling were described. Typical helicopter rescue missions in earthquake relief were divided into three basic types, and the mission flow was carded. The division and function of agents in the helicopter earthquake rescue mission model was introduced, and the agent information layers structure was established. An approach of helicopter earthquake rescue mission effectiveness evaluation, including three types of assessment indicators, was proposed also. Finally, the architecture of a simulation system based on this modeling method was built. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4999